Postcard of Brdo Castle 1930 - Auteur inconnu (Wikimedia Commons, 1930)
Carte postale ancienne issue de Wikimedia Commons. Titre: Postcard of Brdo Castle 1930. Postcard of Brdo Castle.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château; Carte postale